SOME ISSUES OF PROVIDING MEDICAL SERVICES TO THE POPULATION IN RURAL AREAS OF ANDIJAN REGION (Scientific journal of the Fergana State University, 2024)
The article is devoted to the analysis of some indicators of the provision of medical services to the population in rural areas of the Andijan region, the characteristics and factors of its development, the identification of regional differences, the development of scientifically based proposals and recommendations aimed at improving the territorial structure of this system. It used geographical comparison, system-structural, and statistical research.During the study, rural administrative areas were assessed based on grouping according to the provision of hospital and outpatient beds, doctors and paramedical personnel per 10,000 residents. Research has shown that it is necessary to improve the medical care system for the population in rural areas, improve its quality, and strengthen the material and technical base of local medical institutions.